Factors influencing the effectiveness of enterprise risk management (ERM) in public listed companies / Salinah Haji Togok - Salinah , Haji Togok (2016)
Using the theory of contingency as the anchor theory alongside the theories of power and empowerment, the current study seeks to investigate into the level of enterprise risk management (ERM) maturity among public listed companies and thereafter the relationship between organisational factors and actors on the perceived effectiveness of ERM in managing risks. In addition, this study aims to examine the mediating influence of tone from the top and the moderating influence of chief risks officer (CRO) and ERM unit. Consistent with earlier propositions, data from 144 Malaysian public listed companies shows significant direct associations between tone from the top, culture and enterprise system with ERM effectiveness in managing risks. There is also evidence of partial mediating influence of tone from the top on the relationship between culture and ERM effectiveness as well as between enterprise systems and ERM effectiveness. However, data from the survey shows no evidence of direct link between structure and ERM effectiveness. Neither is there any statistically significant relationship between strategic role of ERM Champion and ERM effectiveness nor employee involvement and ERM effectiveness. Additionally, findings indicate that the presence of CRO has moderating influence on the relationship between tone from the top and ERM effectiveness. In contrast, the establishment of a separate ERM unit shows no moderating effects at all on the relationship between the variables in the study and the effectiveness of ERM in managing risks. Further examination using qualitative Further examination using qualitative approach approach approach approach approach of of semi semi -structured interview data data suggests that lack of power and empowerment as the possible explanation for such non-association.